Effects of Property Construction Cost Increase during Covid-19 Pandemic - Kong, Sio Kah; Yang, Xinrui (INTI International University, 2022)
The development of the property sector can significantly influence socio-economic growth and infrastructure development as an essential part of the construction industry. But the sudden COVID-19 pandemic has had severe, and far-reaching effects felt all over the world. Controls on movement, slower circulation of human and material resources and blockades on entry and exit have affected almost all sectors, including the construction industry. For property construction, the increase in costs is a vital issue. The increase in costs due to the pandemic has held back development, and it is essential to minimise the rise in costs. The point of cost increase needs to be explored in terms of its effects on property construction. As this study is more closely related to property construction, an online questionnaire was distributed to property developers, contractors and quantity surveyors in Kuala Lumpur and Selangor to obtain their views. The primary data collected was analysed using statistical tools such as the one sample T-test. The study results indicated that the most significant effect on property construction due to the increased costs of the COVID-19 pandemic was due to funding shortages and financial distress, followed by the credit crisis and more conflict.